Toxicity testing of chitosan from tiger prawn shell waste on cell culture - Maretaningtias Dwi Ariani; Anita Yuliati; Tokok Adiarto (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: A biomaterial used in oral cavity should not become toxic, irritant, carcinogenic, and allergenic. Chitosan represents a new biomaterial in dentistry. Purpose: To examine the toxicity of chitosan from tiger prawn shell waste on cell culture with MTT assay. Methods: Chitosan with concentration of 0.25%, 0.5%, 0.75% and 1% was used in this experiment. Each sample was immersed on eppendorf microtubes containing media culture. After 24 hours, the immersion of media culture was used to examine the toxicity effects on BHK-21 cell based on MTT assay method. The density of optic formazan indicates the number of living cells. All data were then statistically analyzed by one-way Anava. Results: The number of living cells in chitosan from tiger prawn shell waste was 93.16%; 85.07%; 78.48%; 75.66%. Thus, there was no significant difference among groups. Conclusion: Chitosan with 0.25%, 0.5%, 0.75% and 1% concentrations from tiger prawn shell waste were not toxic for BHK-21 cell culture when using parameter CD50.